ON THE HIGH SEA OF SPIRITUALITY. ANTECEDENTS AND DETERMINANTS OF DISCERNMENT AMONG SCHOOL LEADERS IN INDIA - C.A.M. Hermans; F.V. Anthony (Acta Theologica)
Discerning the good is the spiritual compass of living a good life with, and for others. It is the core of “lived spirituality”. A person grows in discernment, when his/her spiritual character traits, spiritual capital and spiritual experiences grow. The authors first map the field of lived spirituality related to discernment. Next, they present the results of a research into lived spirituality of school leaders in India. School leaders have a task to discern the good in school organisations, in order to deliver good education. School leaders in India differ in the level of agreement with discernment. They report higher levels of discernment, if they report a stronger spiritual character trait of self-directed-cooperativeness, more spiritual capital (both claiming the absolute truth of their own religion and/or truth emerging from religious pluralism), and a higher level of mystic experiences.